PENSAR A EDUCAÇÃO ESTÉTICA E A CRIAÇÃO A PARTIR DA VIDA E CANÇÕES DE DONA IVONE LARA - ENMILLY DA COSTA COFFACCI (2025)
The present work “Thinking about aesthetic education and creation based on the life and songs of Dona Ivone Lara” is part of the research line of educational practices, teacher/educator training in school and non-school spaces of the Postgraduate Program in Education of the Federal University of Mato Grosso do Sul – Pantanal Campus (UFMS-CPAN). The object of study of the research is aesthetic education, understood as focused on the development of sensitivity, expressive, imaginative and creative capacity of the person. The general objective of the research was to examine the life and lyrics of Dona Ivone Lara's songs to make visible positions that contribute to the understanding of aesthetic education and creative attitude in the context of education. The specific objectives of the research were: (i) to know the life story (biography) of Dona Ivone Lara, identifying what contributed to her sensitive and creative development; (ii) to understand and visualize processes and/or positions that emanate from. Dona Ivone Lara's musical productions; (iii) to think about aesthetic education and creative attitude considering Dona Ivone Lara's life and compositions. This is a qualitative research with exploratory and descriptive purposes. Operationally, the methodological process included: study of Dona Ivone Lara's biographical works, selection and analysis of Lara's songs, recontextualization of the positions emanating from Dona Ivone Lara's musical productions, or of the interpretations made, in the field of education, with a view to thinking about aesthetic education and creative attitude. The results indicate that aesthetic education develops through the active participation of subjects in experiences with sensitive qualities, and cannot be dissociated from daily school life and social interactions. The importance of experiencing beauty in motivating students is highlighted, enabling the imagination of new scenarios and perspectives. In this sense, art is essential to stimulate the formation of ethical and humanized individuals, not as a teaching tool, but as a means of displacing established logics, boosting critical and collective thinking. As for the creative attitude, research suggests that imagination and creativity are strengthened when emotions and experiences are broadly worked on and expressed. The creative act has its roots in sensitivity and individual repertoires, and is enhanced by dialogue with other experiences and perspectives, enabling the redefinition of meanings and the construction of authentic productions.